حقوق الغريق في الشريعة الإسلامية - رضوان، رفيق أسعد محمد (جامعة فلسطين - عمادة الدراسات العليا والبحث العلمي, 2017)
يتناول هذا البحث الفقهي المقارن موضوعا لم يحظ باهتمام العلماء المعاصرين، وتكلم عنه الفقهاء القدامى في مواضع متناثرة برغم أهميته الكبرى، وهذا الموضوع هو حقوق الغريق، وقد تناولت في هذا البحث مفهوم الغريق ومدى اعتباره من الشهداء ثم تحدثت عن حكم إنقاذ الغريق في الشريعة الإسلامية ثم بينت تدابير الحد من الغرق، ثم تحدثت في المبحث الأخير عن حقوق الغريق بعد موته من غسل وصلاة وميراث، وتوصلت إلى أن إنقاذ الغريق فرض كفاية وتركه إثم، ولابد من اتخاذ التدابير الوقائية للحد منه.
This research deals with an important topic that did not receive the required attention by the contemporary scholars. The earlier scholars, however, discussed it in a brief manner despite its great importance. This topic is the rights of the drowned person. The study discussed the description of the drown person, and his/her consideration as a martyr. The study then discussed the Islamic rulings related to saving the drown person, and the required precautions to avoid being drowned. The last topic of the study presented the rights of the drowned person including rinse, Janaza prayer, and inheritance. Finally, the study concluded by the most important findings and recommendations.
Keywords: الشريعة الاسلامية -- الفقة الاسلامى -- حقوق الغريق